Ten-Year Changes in Bloodstream Infection With Acinetobacter Baumannii Complex in Intensive Care Units in Eastern China: A Retrospective Cohort Study - Meng, Xiao; Fu, Jintao; Zheng, Yue; Qin, Weidong; Yang, Hongna; Cao, Dongming; Lu, Haining; Zhang, Lu; Du, Zhiguo; Pang, Jiaojiao; Li, Wei; Guo, Haipeng; et al. (Frontiers in Medicine, 2021)
Background: There is little evidence on the changing prevalence, microbiological profile and outcome of nosocomial Acinetobacter baumannii complex (ABC) caused bloodstream infection (ABCBSI) specified in intensive care units (ICUs) in long-term studies, especially in China. Objective: We aimed to investigate changes in incidence, antibiotic resistance, therapy and prognosis of ABCBSI in ICUs in eastern China during 2009-2018. Methods: The multicenter retrospective cohort study was conducted and microbiological and clinical data were collected for patients with ABCBSI acquired in nine adult ICUs in eastern China from 2009-2018. Results: A total of 202 cases were enrolled. For the years 2009-2010, 2011-2012, 2013-2014, 2015-2016 and 2017-2018, the incidence of ABCBSI increased significantly, as did the percentage of pandrug-resistant isolates and resistant rates to most of antimicrobial agents; percentage of drug-sensitive isolates decreased (all P <0.05). The frequency of treatment with carbapenems and tigecycline increased and that of cephalosporins decreased. Compared with the first years (2009-2012), ABCBSI patients in latest years (2017-2018) were less often treated with appropriate empiric therapy, more often underwent pneumonia related ABCBSI and mechanical ventilation support, and had higher 28-day mortality rates. Multivariate Cox regression indicated that increasing antibiotics resistant degree of ABC, pneumonia-related ABCBSI and septic shock were risk factors of 28-day death and associated with significant lower survival days. Conclusions: The past decade has witnessed a marked increase in incidence of ABCBSI and in antibiotic resistance, with increasing pneumonia related infections and worrisome mortality in ICUs in China. Controlling increasing resistance and preventing nosocomial pneumonia may play important roles to combat these infections.